2008
DOI: 10.1088/0957-0233/19/9/095403
|View full text |Cite
|
Sign up to set email alerts
|

The µPIVOT: an integrated particle image velocimeter and optical tweezers instrument for microenvironment investigations

Abstract: A novel instrument to manipulate and characterize the mechanical environment in and around microscale objects in a fluidic environment has been developed by integrating two laser-based techniques: micron-resolution particle image velocimetry (μPIV) and optical tweezers (OT). This instrument, the μPIVOT, enables a new realm of microscale studies, yet still maintains the individual capabilities of each optical technique. This was demonstrated with individual measurements of optical trap stiffness (∼70 pN μm −1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Through fluid mechanics, flow-based mechanical test sequences (including shear and extensional loading) may provide control of unique microenvironments when coupled with single cell suspension techniques. The µPIVOT (micron resolution particle image velocimetry combined with optical tweezers) was recently developed to apply controlled multiaxial stresses to single cells suspended with optical tweezers within custom channel designs [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Through fluid mechanics, flow-based mechanical test sequences (including shear and extensional loading) may provide control of unique microenvironments when coupled with single cell suspension techniques. The µPIVOT (micron resolution particle image velocimetry combined with optical tweezers) was recently developed to apply controlled multiaxial stresses to single cells suspended with optical tweezers within custom channel designs [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Eight years later Ozkan et al [44] showed various types of optical manipulation in a microfluidic flow system. More recently, Nè ve et al [45] demonstrated the combination of micrometerresolution particle image velocimetry (mPIV) and optical tweezers in order to manipulate and characterize the mechanical environment in and around microscale objects. They predicted that with this setup, fluid-particle interactions, full field measurements of direct particle-particle interactions, as well as the stress fields around deformed elastic and viscoelastic bodies such as biological cells can be explored.…”
Section: Combination Of Optical Manipulation Techniques With Microflumentioning
confidence: 99%
“…Mejia et al [149] performed thermal probing of E. coli RNA polymerase off-pathway mechanisms. The kinetic mechanism of RNA polymerase (RNAP) revealed a pause-free transcription velocity in the temperature range between 7 to 45 C that was force independent. They suggest that pause entry seems to be a thermally accessible process that presents a maximum at 21 C and conclude that arrest could play a regulatory role in vivo.…”
Section: Force Measurements With Optical Tweezersmentioning
confidence: 99%
“…Simultaneous lPIV and impedance measurements enable simultaneous fluid characterization and real-time monitoring of biological species. The combination of lPIV and optical tweezers (called lPIVOT) was proposed to measure the velocity profile around a trapped suspended particle, which would provide clues toward a better understanding of biological cells suspended in a fluid medium (Neve et al 2008). It was reported that when the trapped particle with diameter between 15 and 35 lm was exposed to fluid flow from 50 lm s -1 to 500 lm s -1 , the influence of optical tweezers acting on the tracer particles can be neglected.…”
Section: Other Applicationsmentioning
confidence: 99%